2020
DOI: 10.3389/fgene.2020.00363
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immune-Related Gene Signature for Risk Stratification and Prognosis of Survival in Lower-Grade Glioma

Abstract: Objective: Despite several clinicopathological factors being integrated as prognostic biomarkers, the individual variants and risk stratification have not been fully elucidated in lower grade glioma (LGG). With the prevalence of gene expression profiling in LGG, and based on the critical role of the immune microenvironment, the aim of our study was to develop an immune-related signature for risk stratification and prognosis prediction in LGG. Methods: RNA-sequencing data from The Cancer Genome Atlas (TCGA), Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 61 publications
5
112
1
Order By: Relevance
“…Zhang et al identified six immune-related genes (CANX, HSPA1B, KLRC2, PSM C6, RFXAP, and TAP1) as risk signatures. Importantly, Kaplan-Meier and ROC curves, as well as risk plotting, verified their performance in TCGA and CGGA datasets 28 . Zhang et al observed that a high immune score was associated with low methylation and copy number variation levels, a high expression of immunosuppressive markers (CD27, PDL1 and CTLA4), and a shorter recurrence-free survival 29 .…”
Section: Discussionmentioning
confidence: 68%
“…Zhang et al identified six immune-related genes (CANX, HSPA1B, KLRC2, PSM C6, RFXAP, and TAP1) as risk signatures. Importantly, Kaplan-Meier and ROC curves, as well as risk plotting, verified their performance in TCGA and CGGA datasets 28 . Zhang et al observed that a high immune score was associated with low methylation and copy number variation levels, a high expression of immunosuppressive markers (CD27, PDL1 and CTLA4), and a shorter recurrence-free survival 29 .…”
Section: Discussionmentioning
confidence: 68%
“…For example, Deng et al [34] found up to 397 IRGs were signi cantly associated with LGG survival. Zhang et al [21] established a risk model based on 6 IRGs (CANX, HSPA1B, KLRC2, PSMC6, RFXAP, and TAP1). However, one common disadvantage of all the above assays lies in standardizing gene expression pro les, which is di cult to avoid.…”
Section: Discussionmentioning
confidence: 99%
“…Immune-checkpoint inhibitors and immunotherapy play a part in improving gliomas prognosis [15,16]. As to prognosis biomarkers, researchers have explored the possibility of stratifying patients with malignant tumors (including gliomas) based on gene expression pro les and have constructed a multigene-expression model that can be applied to stratify high-risk subgroup [17][18][19][20][21][22]. One common drawback of the above studies is that gene expression pro les require suitable normalization.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, gene expression pro les and clinical information of 214 patients with SKCM from the Gene Expression Omnibus (GEO) GSE65904 corhort (https://www.ncbi.nlm.nih.gov/geo/) were downloaded as a validation cohort [34]. All gene expression les were log2-transformed, and pro les from different platforms were normalized using the R package "sva" to remove batch effects reported by previous studies [35,36]. Furthermore, 1399 protein domains of OS were downloaded from the GeneCards database (https://www.genecards.org) with relevance score ≥ 7, and subsequently applied for further exploration.…”
Section: Data Acquisitionmentioning
confidence: 99%